TINGKAT PEMAHAMAN MAHASISWA TERHADAP PENGGUNAAN PINJAMAN ONLINE YANG MARAK DI LINGKUNGAN GEN Z - Nugraha, Muhamad Arya Nugraha; Hatimatunnisani, Hani; Irianti, N. Anti Nur; Dewi, Yeni Amanda; Haryono, Rakhmat (Jurnal Sosio dan Humaniora (SOMA), 2025)
Online lending services are a form of digital financial innovation that enables users to quickly access funds without the need for collateral. This study aims to explore the extent of students’ understanding regarding the widespread use of online loans among Gen Z. A descriptive approach was employed, utilizing questionnaires and interviews involving 60 students from a private university in Bandung. The increasing trend of online loan usage among students is driven by a consumerist lifestyle, social pressure, and limited awareness of associated risks and interest rates. Poor financial literacy can lead to negative consequences such as debt accumulation, financial stress, and mental health issues. Therefore, more intensive financial education efforts are essential to raise awareness and improve students’ financial literacy regarding the responsible use of online lending platforms.